2022
DOI: 10.3390/ijms24010171
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Joint Osteoarthritis: Pathogenic Mechanisms Involving the Cartilage and Subchondral Bone, and Potential Therapeutic Strategies for Joint Regeneration

Abstract: The temporomandibular joint (TMJ) is a specialized synovial joint that is crucial for the movement and function of the jaw. TMJ osteoarthritis (TMJ OA) is the result of disc dislocation, trauma, functional overburden, and developmental anomalies. TMJ OA affects all joint structures, including the articular cartilage, synovium, subchondral bone, capsule, ligaments, periarticular muscles, and sensory nerves that innervate the tissues. The present review aimed to illustrate the main pathomechanisms involving cart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 189 publications
0
29
0
Order By: Relevance
“…Therefore, finding and defining joint injury drivers will be a breakthrough solution. Lately, numerous studies suggested that subchondral bone remodelling occurs prior to cartilage injury due to altered joint stress distribution and mechanical structural imbalance 37–40 . Simultaneously, a significant distribution of neovascularization in the subchondral bone after OA injury was observed in both human and animal samples 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, finding and defining joint injury drivers will be a breakthrough solution. Lately, numerous studies suggested that subchondral bone remodelling occurs prior to cartilage injury due to altered joint stress distribution and mechanical structural imbalance 37–40 . Simultaneously, a significant distribution of neovascularization in the subchondral bone after OA injury was observed in both human and animal samples 30 .…”
Section: Discussionmentioning
confidence: 99%
“…These pathologic changes could further lead to mandibular movement dysfunction and other severe complications. [42][43][44][45] TNF-α and other cytokines such as IL-1β induced by TNF-α regulate the chondrocyte reaction and mediate cartilage destruction. 46,47 TNF-α-induced inflammation is closely correlated with bone and cartilage degradation as a result of degradative enzymes released from joint tissues.…”
Section: Bone and Cartilage Metabolismmentioning
confidence: 99%
“…112 The subchondral bone actively participates in TMJOA through an abnormal bone remodeling initially characterized by a loss of bone mass, followed by reparative mechanisms that lead to stiffness and thickening of the condylar osteochondral interface. 43 Due to the unique biological properties of subchondral bone and cartilage, developing a tissue engineering scaffold that can promote dual-lineage regeneration of cartilage and bone simultaneously remains a great challenge. Recently there have been many experiments based on hydrogels for osteochondral repair of TMJ.…”
Section: Osteochondral Repair and Regeneration Of Tmjmentioning
confidence: 99%
“…On this basis, determining the structure and mechanical mechanism of naturally minimizing the stress concentration at the osteochondral interface not only provides a platform for the design of potential soft−hard interfaces but also may generate relevant insights to guide the understanding of the pathogenesis and treatment mode of TMJ diseases. 6,7 In this study, we focused on the structural, compositional, and mechanical transitions in the osteochondral interface of the TMJ. We collected a total of 20 samples of porcine condyles from 10 pigs, and it has been well documented that the porcine TMJ is very similar to the human TMJ, making it an ideal animal model.…”
mentioning
confidence: 99%
“…Further investigations are needed to elucidate the precise biomolecular composition of this interfacial tissue and characterize the detailed stiffness transitions. On this basis, determining the structure and mechanical mechanism of naturally minimizing the stress concentration at the osteochondral interface not only provides a platform for the design of potential soft–hard interfaces but also may generate relevant insights to guide the understanding of the pathogenesis and treatment mode of TMJ diseases. , …”
mentioning
confidence: 99%